Research and Enlightenment of Expanding Economic Benefits of Professional Sports League – Take NBA as an Example - Li, Chenyu; Tian, Libin; Yu, Jiaru; Zhou, Yilong (Transactions on Economics, Business and Management Research, 2024)
With the continuous development of economy, society and national economy, the public’s attention and interest in sports increase, the professional sports league as become a new growth point of the national economy in the whole country, and the economic benefits generated by it are increasing day by day in the world. The rapid economic development of professional sports alliances has promoted the prosperity of the sports industry. The highly commercial operation mode and makes profits through ticket sales, media broadcast rights, sponsor cooperation and other ways. The high income of star athletes has a significant impact on the economic and social influence of the alliance. Taking NBA as an example to analyze how professional sports leagues expand the market. In the past, it were summarized and further studied. This paper will study the development ideas and strategies of NBA, to achieve a comprehensive understanding of the profit model of professional sports leagues, and to provide reference for the development of other sports leagues.